KOMUNIKASI PERSUASIF GURU DALAM MEMBANGUN KREATIVITAS ANAK USIA DINI PADA TK MELATI PUTIH DESA BUKIT KRATAI - Adi Setyawan; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This the is under the guildance of father Ir. Rusmadi Awza, S.Sos, M.SiWhite jasmine TK school is the frits school kindergarten in the village Kratai hill. Inthis study the quthors wanted to see how persuasive comunication teacher in earlychildhod creativity to build on TK White Jasmine.As for the purpose of this research is to know: 1) learning methodsapplied at school TK White Jasmine. 2)To devermine the components of the learningcurriculum that is in White Jasmine TK. Research uning descriptive qualitatifresearch method informen that has been set using purposive sampling method amongthe principal TK, TK two permanent teachersin budget parents, students TK WhiteJasmine. Data celecting interviews, observation, and documentation. Results of thestudy stated that the method applied learning school TK White Jasmine.so buildchildren creativity in developthing their thinking at an early agel. The learningmethods inclued : preparation of teachers in the learning process, control andassesment techniquen, build confidance in learning, learning how to build creativitychildren. And the role of theachers in a creative game in curriculum componentsapplied in school TK White Jasmine include : the development of the curriculumstucture, curriculum, princeples of curriculum development,aswellascomponentofthecurriculum.Keywood : Communication teacher in kreativity childhood